Meanings attributed to complications of ostomy and skin peristhectomy in a public reference service in the Cariri region (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: To present the meanings attributed by participants or their caregivers in relation to complications of the ostomy and peristomal skin in a referral service in the Cariri region. Methods: Descriptive research, of a qualitative nature, composed of 24 participants with intestinal ostomies. The data were collected in the period of March and June of 2018 in the Service of Health Care of the Person with Ostomy located in the city of Juazeiro do Norte, state of Ceará. The interviews were guided by a structured script and recorded through a mobile app. During the data analysis, participants’ answers were transcribed in its full. Results: From the report of the participants, the following meanings for the complications of the ostomy and peristomal skin emerged: aspects related to the quality of the collecting equipment, such as time of permanence of the bag, type of bag and adhesiveness; fragility in the educational process; and effectiveness of surgical procedures. Conclusion: The provision of specialized assistance is necessary so that the orientations of the professionals are directed to the individual needs of each participant, since health care is based on an interpersonal process centered on the integral care of the individual and his or her family.